2018
DOI: 10.14236/ewic/hci2018.143
|View full text |Cite
|
Sign up to set email alerts
|

Use of Low-Resolution Infrared Pixel Array for Passive Human Motion Movement and Recognition

Abstract: The daily monitoring of ageing population is a current issue which can be effectively tackled by applying daily activity monitoring via smart sensing technology. The purpose of the monitoring is mostly aimed at collecting health conditional related activity awareness and emergency events detection. This is a pilot study that uses low pixel resolution infrared sensors for nonintrusive human activity detection and recognition without body attachments and taking of individual image. In this work, we design and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Around the same time, Basu and Rowe [2] showed that the same camera can be used to detect multiple people and track their motions as well as estimate the directions of movement. In a similar field, Tao et al [4] and Karayaneva et al [5] also proposed hand-crafted features that could be used in recognizing actions. A common denominator of all these works is the fact that they rely on handcrafted features in order to carry out the tasks.…”
Section: Action Recognition Based On Tpamentioning
confidence: 99%
“…Around the same time, Basu and Rowe [2] showed that the same camera can be used to detect multiple people and track their motions as well as estimate the directions of movement. In a similar field, Tao et al [4] and Karayaneva et al [5] also proposed hand-crafted features that could be used in recognizing actions. A common denominator of all these works is the fact that they rely on handcrafted features in order to carry out the tasks.…”
Section: Action Recognition Based On Tpamentioning
confidence: 99%
“…The ultra low-resolution IR images were used in some works. Researchers have applied SVM, RF and KNN on low-resolution raw pixels data and achieved 84.2% overall accuracy [12]. In [34], a Y/N fall detection strategy was developed based on a KNN framework using spatio-temporal pixel level statistics.…”
Section: B Learning-based Featuresmentioning
confidence: 99%
“…A comparison of the recognition accuracy is performed between each of the SDA and SPCA techniques and their corresponding non-sparse feature extraction methods, Reduced Rank LDA (RRLDA) [10] and Principal Component Analysis (PCA). Reviewing the existing pilot studies [9], [11], [12] on low resolution images for activity monitoring in healthcare projects however, no detailed analysis of the features of this new type of data based on sparse techniques and their tolerance to noise was found.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IR devices represent an attractive solution to be deployed in care homes and hospitals. Current studies reveal significant recognition rates (>90%) for activities including standing, sitting, walking, falling, and others [13], [14], [15]. Contrarily to their advantages, IR devices suffer from a relatively low detection distance.…”
Section: Introductionmentioning
confidence: 99%